Women perspective in the future of Sami reindeer husbandry (In Norwegian with Summary in English) - Joks, Solveig (Rangifer, 2005)
Women's traditional tasks are invisible in the official image of reindeer husbandry. The reindeer husbandry nowadays is represented as a meat producer, and the official documents are focused on the work with the reindeer herd. Traditionally, work with the herd and slaughtering belonged to men. In focusing only on certain tasks in the total industry, a lot of other important and necessary work will remain invisibly. A myth that reindeer husbandry is only for men arises easily, too. Bureaucrats, researchers and others who participate in the official debates on reindeer husbandry strengthen this myth. Since women and their tasks are not much visible in the official view of reindeer husbandry, they are indirectly defined outside the reindeer keeping and its activities. However, reindeer husbandry is more manifold than the official documents are presenting. Women's invisibility in the official image of reindeer husbandry strengthens further since only 17% of the production units are registered on women. Though the Reindeer-Management Act of 1996 was changed in the way that spouses together can be owners of a production unit, most men are still registered as leaders of the units. As a main rule, unmarried women and women who are married with men without production units have their herd under their father's or brother's unit. Thus, most women are formally under the leadership of men. Women's legal position is therefore weak since the rights of reindeer husbandry today are connected closely to the production unit. In leaving out important tasks and to describe reindeer husbandry as a work for only men can give a wrong image of reindeer husbandry and this false impression is strengthened when often repeated.